Detailed cross-sectional study of 60 superficial femoral artery occlusions: morphological quantitative analysis can lead to a new classification - Ohana, Mickaël; El Ghannudi, Soraya; Girsowicz, Elie; Lejay, Anne; Georg, Yannick; Thaveau, Fabien; Chakfe, Nabil; Roy, Catherine (Cardiovascular Diagnosis and Therapy, 2014)
Objective: Current clinical classification of superficial femoral artery (SFA) occlusions as defined by TASC II guidelines is limited to length and calcifications analysis on 2D angiograms, while state-of-the-art cross-sectional imaging like computed tomography angiography (CTA) and magnetic resonance angiography (MRA) provides much more detailed anatomical information than traditional invasive angiography: quantitative morphological analysis of these advanced imaging techniques could therefore be the basis of a refined classification. Methods and results: Forty-six patients (65% men, 68±11.6 years) that underwent lower limb CTA were retrospectively included, totalizing 60 SFA occlusions. Lesions were classified as TASC II stage A in 3% of cases, stage B in 20%, stage C in 2% and stage D in 75%. For each pathological artery, curved multiplanar reconstructions following the occluded SFA course were used to measure the total length and the mean diameter of the occluded segment. Color-coded map provided an accurate estimation of calcifications' volume. Thirty-nine percent of the occlusions were total. Mean occluded segment length was 219±107 mm (range, 14-530 mm); mean occluded segment diameter was 6.1±1.6 mm (range, 3.4-10 mm); mean calcifications' volume in the occluded segment was 1,265±1,893 mm3 (range, 0-8,815 mm3), corresponding to a percentage of 17.4%±20% (range, 0-88.7%). Shrinked occluded occlusions were defined by a mean diameter under 5 mm and heavily calcified occlusions by a mean percentage of calcifications above 4%. Use of these thresholds allowed the distinction of four groups of patients: heavily calcified occlusions with preserved caliber (56%), non-calcified occlusions with preserved caliber (19%), non-calcified occlusions with small caliber (15%) and heavily calcified occlusions with small caliber (10%). Conclusions: SFA occlusions are disparate: this simple morphological study points out TASC II classification weaknesses for SFA occlusions, as quantitative cross-sectional imaging analysis with measurement of mean occluded diameter and percentage of calcifications can refine it. This could be particularly useful in the management of TASC II type D lesions, for which new endovascular revascularization techniques are arising, and where a CTA or MRA-based morphological classification could provide support in choosing between them.